2021
DOI: 10.1071/fp21241
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide effectively orchestrates postharvest flower senescence: a case study of

Abstract: Nitric oxide releasing compound sodium nitroprusside (SNP) is regarded as novel chemical to beat the daunting challenges of postharvest losses in cut flowers. In the recent years, it has yielded propitious results as postharvest vase preservative for cut flowers. Our study explicates the efficacy of SNP in mitigating postharvest senescence in Consolida ajacis (L.) Schur cut spikes. The freshly excised C. ajacis spikes were subjected to different SNP treatments viz, 20 μM, 40 μM, 60 μM and 80 μM. The control sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…However, the effects of GSNOR and NO on soluble sugar and soluble protein accumulation are different. A previous study found that NO alleviated postharvest senescence in Consolida ajacis cut flowers by improving the levels of sugars, phenols and soluble proteins [ 41 ]. Nevertheless, another report found that the bioproduction of sugars, organic acids, and amino acids was mildly influenced by exogenous NO and indirectly stimulated GSNOR during tomato storage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of GSNOR and NO on soluble sugar and soluble protein accumulation are different. A previous study found that NO alleviated postharvest senescence in Consolida ajacis cut flowers by improving the levels of sugars, phenols and soluble proteins [ 41 ]. Nevertheless, another report found that the bioproduction of sugars, organic acids, and amino acids was mildly influenced by exogenous NO and indirectly stimulated GSNOR during tomato storage [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an early proteomic study of potential targets of S -nitrosation in potato tuber samples treated with the NO donor S -nitrosoglutathione (GSNO), it was possible to identify 80 protein candidates and, among them, was found a LOX protein [ 52 ]. The NO treatment of the cut Consolida ajacis flower during postharvest storage triggered a decrease in LOX activity, which alleviated its deterioration since the NO promoted the membrane stability [ 53 ]. In Arabidopsis, NO induces the expression of the LOX3 gene, which leads to JA production [ 54 ].…”
Section: Discussionmentioning
confidence: 99%